The deadweight cost of implementation of the Foreign Account Tax Compliance Act (FATCA) - Brodzka, Alicja (Koszty implementacji FATCA, 2014)
From 1 June 2013 FATCA – the new American law on the disclosure of financial information about foreign accounts for tax purposes – came into force. The aim of the Foreign Account Tax Compliance Act is to prevent the tax evasion of US citizens with offshore accounts. The Act requires all foreign financial institutions to identify American people in possession of the financial accounts (banking, brokerage, etc.), and then transmit that information to the tax authorities of the United States. The penalty for failure to comply with this requirement will be a 30% withholding tax on capital flows from the United States. The article presents the main issues connected with FATCA and brings closer the arguments pro and contra. As the Act results in new requirements which non-US financial institutions have to fulfil, the paper looks both at the legislative and cost-related problems. It also analyses how the new provisions will influence Polish financial institutions and their customers
Nauki o Finansach = Financial Sciences, 2014, Nr 4 (21), s. 11-22
Keywords: FATCA; exchange of tax information; international tax law; foreign financial institutions; wymiana informacji podatkowych; międzynarodowe prawo podatkowe; zagraniczne instytucje finansowe